The Shocking Story of Electricity - Anna Claybourne (London, United Kingdom Usborne Publishing Ltd, 2006)
This is a new and exciting non-fiction title in the hugely successful "Usborne Young Reading" series, which aims to encourage independent reading with a variety of engaging and informative subjects. "The Shocking Story of Electricity" is an illuminating exploration of an essential power source from earliest experiments to the gadgets and gizmos of the modern world. The title is vividly illustrated and authored, and is clearly laid out with speech bubbles to aid the narrative flow. The Usborne Young Reading programme was developed in conjunction with educational experts at the University of Surrey. These titles form part of series two, which is aimed at young readers who are growing in confidence.
Keywords: Narrative Nonfiction -- Narrative Nonfiction